Recommendations for hamstring injury prevention in elite football: translating research into practice - Buckthorpe, M.; Wright, S.; Bruce-Low, S.; Nanni, G.; Sturdy, T.; Gross, A. S.; Bowen, L.; Styles, B.; Della Villa, S.; Davison, M.; Gimpel, M. (British Journal of Sports Medicine, 2018)
Introduction: Injuries in football exert negative impacts on team performance and club finance. Hamstring strain injuries (HSI) are consistently the most prevalent time loss injury in football and as such are an important issue in football medicine. Despite an ever-increasing wealth of information emerging on the aetiology of HSIs, their incidence in football is increasing. This could be explained by the increased intensity and physical demands of football match play over the last decade; but practitioners should also question their approach to injury prevention and physical preparation of players, an area where research is lacking. There is an evidence-based strategy to prevent HSIs, however, there appears to be a large disconnect between this available evidence and its adoption in elite football. For example, the Nordic hamstring exercise (NHE) programme has been shown to effectively reduce HSIs by 65%-70%. But recent surveys of elite European Champions League (n=32) and Norwegian Premier League (n=18) teams showed that only 11% of these teams fully adopt the programme. Within elite football, there is a large disconnect between evidence-based practice and the actual interventions used by science and medical teams to prevent injuries. In line with an emerging body of evidence-based research, we believe that preventing HSIs in elite football requires a holistic approach, which considers multiple risk factors and their inter-relations, implemented effectively. In designing our injury prevention programme, we combine both the theory and the available evidence on HSI risk factors and intervention studies, as well as considering the context surrounding the player when designing our overall injury prevention approach. Abstract from author